KUE BANGKIT KHAS MELAYU RIAU DARI UBI JALAR UNGU (Ipomoea batatas L) SEBAGAI MAKANAN FUNGSIONAL BALITA GIZI KURANG DI WILAYAH KERJA PUSKESMAS BENGKALIS - Junita Zulfitrianna, Astry; Ekdeni Aifa, Wira; Susanti, Komaria; Yanti, Rifa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Malnutrition has been the biggest problem for the last 5 years. As a result of these nutritional problems, such as physical growth failure, less than optimal growth and intelligence, can even cause death in toddlers. To determine the effect of giving bangkit cake from purple sweet potato flour (Ipomoea batatas L) as an alternative functional food for toddlers with malnutrition in the Bengkalis Health Center Work Area. The type of research is pre-experiment with the research design used in this study is one group pre-test post-test design. The population in this study was 75 toddlers who experienced malnutrition with a sample size of 45 toddlers. The sampling technique used Purposive Sampling. The instruments used were intervention sheets, Scales, SOPs and observation sheets. Data processing of statistical tests T-Test. Dependent T-Test used is the Paired Samples Test. The results of the study were the weight of toddlers before being given bangkit cake from purple sweet potato flour (Ipomoea batatas L) on average = 11.507 kg. The weight of toddlers after being given bangkit cake made from purple sweet potato flour (Ipomoea batatas L) averaged = 12.549 kg and there was an effect of giving bangkit cake made from purple sweet potato flour (Ipomoea batatas L) as a functional food for undernourished toddlers in the Bengkalis Health Center Work Area with a p-value = 0.000. The output of the study is a Journal. It is concluded that the Riau Malay special Kue Bangkit made from purple sweet potatoes can be used as functional food for undernourished toddlers. It is hoped that they will be more responsive to the nutritional status of children by conducting regular posyandu checks, especially for mothers who have toddlers so that they can monitor their children's growth and development routinely. Keywords: Malnutrition, rose cake, purple sweet potato.